2013
DOI: 10.1007/s00284-012-0300-7
|View full text |Cite
|
Sign up to set email alerts
|

Virgibacillus natechei sp. nov., A Moderately Halophilic Bacterium Isolated from Sediment of a Saline Lake in Southwest of Algeria

Abstract: A novel, Gram-positive, moderately halophilic bacterium, oxidase- and catalase-positive designated FarD(T) was isolated from sediments of a saline lake located in Taghit, 93 km from Bechar, southwest of Algeria. Cells were rod-shaped, endospore forming, and motile. Growth occurred at 15-40 °C (optimum, 35 °C), pH 6.0-12.0 (optimum, 7.0) and in the presence of 1-20 % NaCl (optimum, 10 %). Strain FarD(T) used glucose, mannitol, melibiose, D-mannose, and 5 ketogluconate. The polar lipids comprised diphosphatidylg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The type strain of Virgibacillus natechei is FarD T (DSM 25609 T or CCUG 62224 T ) [5]. As reported previously by the authors [5], strain FarD T was maintained at 35°C on Sehgal and Gibbons medium (SG) containing the following (in g/L): casamino acids, 7.5; yeast extract, 10; sodium glutamate, 1; trisodium citrate, 3; MgSO 4 ·7 H 2 O, 20; KCl, 2; FeSO 4 ·7 H 2 O, 0.036; and MnCl 2 ·4 H 2 O, 0.00036 supplemented with 100 g/L of NaCl at pH 7. After incubation at 35°C, a halo of casein degradation was revealed around the colony growth onto skimmed milk agar plates, as well described previously by the authors [17, 18].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The type strain of Virgibacillus natechei is FarD T (DSM 25609 T or CCUG 62224 T ) [5]. As reported previously by the authors [5], strain FarD T was maintained at 35°C on Sehgal and Gibbons medium (SG) containing the following (in g/L): casamino acids, 7.5; yeast extract, 10; sodium glutamate, 1; trisodium citrate, 3; MgSO 4 ·7 H 2 O, 20; KCl, 2; FeSO 4 ·7 H 2 O, 0.036; and MnCl 2 ·4 H 2 O, 0.00036 supplemented with 100 g/L of NaCl at pH 7. After incubation at 35°C, a halo of casein degradation was revealed around the colony growth onto skimmed milk agar plates, as well described previously by the authors [17, 18].…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of bacterial diversity of an Algerian saline lake revealed the presence of a novel specie of a genus Virgibacillus , namely Virgibacillus natechei sp. nov., strain FarD T with unusual phenotypic and genotypic characteristics [5]. In fact, the strain FarD T was mesophilic, moderately halophilic, and alkaliphilic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also considered to be one of the less explored parts. Our team has been interested in these magnificent ecosystems for many years and the few studies that have been published have shown great active biomolecules [16–18], biodiversity of interesting new taxa [1924], and enzymes [25, 26]. …”
Section: Introductionmentioning
confidence: 99%
“…At the time of writing, the genus Virgibacillus comprises 26 species with validly published names (http://www.bacterio.net/uw/virgibacillus. html); two other species, designated 'Virgibacillus zhanjiangensis' (Peng et al, 2009) and 'Virgibacillus natachei' (Amziane et al, 2013), have been proposed, but these names have not been validly published. Phylogenetically related genera are Oceanobacillus, Ornithinibacillus, Lentibacillus, Paucisalibacillus and Cerasibacillus.…”
mentioning
confidence: 99%